Kepuasan Pasien di Poliklinik Gigi dan Bedah Mulut di Rumah Sakit - Maya Monalisa, Sarah; Anggreny, Dian Eka; Rawalillah, Hamyatri (Avicenna: Jurnal Ilmiah, 2025)
Background: Consumer satisfaction is closely related to service quality. The standard for patient satisfaction in health services is set nationally by the Ministry of Health of the Republic of Indonesia, with a minimum of patient satisfaction of above 95% (Ministry of Health of the Republic of Indonesia, 2016). The results of a survey of public satisfaction with Hospital services in South Sumatra from January to June 2022 showed a survey result with a value of 88.18 (very good). Method: This type of research is quantitative with an analytical survey design with a cross-sectional approach, the population is patients at the Dental and Oral Surgery Polyclinic of Martapura OKU Timur Hospital with sample of 59 respondents and the sampling technique is accidental sampling. Univariate, and bivariate data analysis Result : Based on the results of univariate analysis, it was found that women (91.5%), young age (57.6%), higher education (55.9%), dissatisfied (64.4%), poor tangible (54.2%), poor reliability (69.5%), poor responsiveness (74.6%), poor assurance (79.7%), and poor empathy (71.2%). The results of statistical tests using chi square showed a relationship between tangible (p value 0.000), reliability (p value 0.000), responsiveness (p value 0.003), assurance (p value 0.002), empathy (p value 0.000) and patient satisfaction. Conclusion : Conclusion of the existence of a real relationship, reliability, responsiveness, assurance, empathy with patient satisfaction. It is expected that health workers in Hospital area will further improve the quality of service in order to increase patient satisfaction. Keywords: Patient satisfaction, service quality, hospital